ANTHROPOCENTRIC APPROACH AND THE TRANSFORMATION OF THE LEGAL SUBJECT IN THE DIGITAL AGE: CHALLENGES FOR LABOR LAW - Razieva Динара Багдатовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
Recent advances in artificial intelligence and robotics have led to the emergence of technological solutions capable not only of performing tasks, but also of making autonomous decisions, adapting to changing conditions, and interacting with other entities. In this regard, researchers are faced with the question of whether such systems can be recognized as subjects of law. This study is based on the anthropocentric approach, according to which the human being is recognized as the highest value and the primary reference point for legal regulation. By applying philosophical-anthropological, comparative legal, and functional-analytical methodologies, the author explores the limitations of traditional legal understanding in the digital era and argues against the recognition of intelligent agents as subjects of labor law. The focus is placed on preserving the ontological and legal primacy of the human in new labor formats, while proposals are formulated for the normative designation of intelligent systems as tools of labor. The article substantiates the need to modernize labor legislation to ensure the safety, sustainability, and ethical nature of human–technology interaction. The author draws special attention to the risks associated with replacing the human being in the legal regulation of labor and presents scientific concepts that allow for the possibility of creating “techno-subjects.” The article substantiates the need to legally define intelligent systems as tools of labor and proposes specific amendments to the Labor Code of the Republic of Kazakhstan aimed at regulating the safety of interaction with intelligent and robotic systems. It is concluded that the adaptation of labor law should be based not on the rejection of anthropocentrism, but on its conceptual renewal. The human being must remain the central figure of the legal system, while technology should serve as a means of realizing human labor potential.